Cement Distribution System in CV. Indosatu With a Supply Chain Management Approach - Dede Serlina; Anggun Fergina; Ivana Lucia kharisma (Universitas Nahdlatul Ulama Surabaya, 2022)
CV. Indosatu, which is engaged in building material, a three-wheel cement distributor, has more than 80 customers for building shops and projects located in the Sukabumi city and district areas, so a sales and delivery information system is needed that helps customers and receives fast information, as well as for sales. and the admin will make it easier for orders received from the store and forwarded to the admin section to be verified for further delivery by the logistics section, for sales and stock data information it will be easier to get too.This system will be built using PHP Nativ framework, JavaScript, CSS and MySQL databaseThe final result obtained is a system with (SCM) Supply Chain Management used by CV. Indosatu. This system is able to provide information about orders from sales, store information, shipping information and stock information. From the test results on users, it shows that this marketing and logistics management system helps in processing sales data and processing stock shipping data.